The relationship between self-rated health and subsequent health outcomes over the decades among older Individuals in the United States - Wong, Shawn Jun Kit (Nanyang Technological University, 2024)
Objectives: Existing research has established significant associations between Self-Rated Health (SRH) and subsequent health outcomes such as mortality and morbidity. However, limited research has examined associational changes between Self-Rated Health and these health outcomes. Drawing from the framework of health evaluation, associational changes may arise from both reductions and improvements in accuracy of health evaluations. The study therefore seeks to investigate associational changes between Self-Rated Health and subsequent health outcomes in the American context.